Uncertainties quantification and modelling of different rheological models in estimation of pressure losses during drilling operation - P. A. L, Anawe; Adewale, Folayan J. (International Journal of Engineering and Technology, 2018)
The determination of pressure losses in the drill pipe and annulus with a very high degree of precision and accuracy is sacrosanct for proper pump operating conditions and correct bit nozzle sizes for maximum jet impact and forestalling of possible kicks and eventual blow outs during drilling operation. The two major uncertainties in pump pressure estimation that are being addressed in this research work are the flow behavior index (n) and the consistency index factor (k). It is in this light that the accuracy of various rheological models in predicting pump pressure losses as well as the uncertainties associated with each model was investigated.Â In order to come by with a decisive conclusion, two synthetic based drilling fluids were used to form synthetic muds known as sample A and B respectively. Inference from results shows that the Newtonian model underestimated the pump pressure by 78.27% for sample A and 82.961% by for sample B. While the Bingham plastic model overestimated the total pump pressure by 100.70% for sample A and 48.17% for sample B. Three different power law rheological model approaches were used to obtain the flow behavior index and consistency factor of the drilling fluids. For the power law rheological model approaches, an underestimation error of 23.5743% was encountered for the Formular method for sample A while the proposed consistency index averaging method reduces the error to 14.9306%. The Graphical method showed a reasonable degree of accuracy with underestimation error of 5.6435%. Sample B showed an underestimation error of 47.8234% by using the power law formula method while the Consistency averaging method reduced the error to 20.7508. The graphical method showed an underestimation error of 0.4318%.